ETIKA DAN PENGGUNAAN GENERATIVE ARTIFICIAL INTELLIGENCE OLEH SISWA SEKOLAH MENENGAH: TINJAUAN LITERATUR SISTEMATIS - Hendry, dedy; Sumartiningsih, Sri Sumartiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article presents a systematic literature review with a PRISMA-informed narrative synthesis on the ethical use of generative artificial intelligence (GenAI) by lower- and upper-secondary students. Searches were directed to Scopus, ERIC, DOAJ, SINTA, and Moraref for publications from 2023 to March 2026, with emphasis on downloadable full texts discussing student use, academic integrity, AI literacy, cognitive implications, and school policy. Forty-five documents met the inclusion criteria. The synthesis identifies three recurrent patterns. First, GenAI is used primarily to accelerate procedural work, including brainstorming, essay revision, translation, step-by-step support in mathematics, and assistance in programming tasks. Second, the boundary between legitimate learning support and academic misconduct is increasingly blurred because GenAI can generate fluent outputs that conceal limited student reasoning and authorship. Third, institutional responses remain uneven; many schools oscillate between prohibition and uncritical adoption while still lacking coherent guidance on disclosure, assessment design, data protection, and teacher development. Overall, the literature suggests that GenAI should be positioned as a supervised learning aid rather than a substitute for students’ intellectual work. For Islamic junior secondary schools and madrasah, the review proposes a character-based AI literacy orientation that aligns responsible technology use with honesty, accountability, verification, and disciplined thinking